Prospects for the application of pathological response rate in neoadjuvant therapy for gastric cancer - Bao, Zicheng; Jia, Nan; Zhang, Zhidong; Hou, Chenyu; Yao, Bin; Li, Yong (Frontiers in Oncology, 2025)
With the annual increase in the incidence and mortality rates of gastric cancer, it has gradually become one of the significant threats to human health. Approximately 90% of gastric cancer patients are diagnosed with adenocarcinoma. Although the 5-year survival rate for early-stage gastric cancer can exceed 90%, due to its concealed symptoms, less than half of the patients are eligible for radical surgical treatment upon diagnosis. For gastric cancer patients receiving palliative treatment, the current expected survival time is only about one year. In China, the majority of gastric cancer patients, accounting for about 80% of the total, are in the locally advanced stage. For these patients, radical surgery remains the primary treatment option; however, surgery alone is often inadequate in controlling tumor progression. In the pivotal MAGIC study, the recurrence rate was as high as 75%, and similar results were obtained in the French ACCORD07-FFCD9703 study. Numerous clinical trials are currently exploring preoperative neoadjuvant therapy for patients with locally advanced gastric cancer. Data indicates that preoperative neoadjuvant therapy can not only reduce the size of the local tumor but also shrink surrounding lymph nodes, thereby downstaging the tumor and improving the R0 resection rate. Additionally, it can decrease tumor cell activity and eliminate potential micrometastases. The emergence of various immunotherapies has ushered in a new era for neoadjuvant treatment options for gastric cancer.